2019
DOI: 10.30536/j.ijreses.2018.v15.a3074
|View full text |Cite
|
Sign up to set email alerts
|

Observing the Inundated Area Using Landsat-8 Multitemporal Images and Determination of Flood-Prone Area in Bandung Basin

Abstract: Flood is the most frequent hydro-meteorological disaster in Indonesia. Flood disasters in the Bandung basin result from increasing population density, especially in the Citarum riverbank area, accompanied by land use changes in upstream of the Citarum catchment area which has disrupted the river’s function. One of the basic issues that need to be investigated is which areas of the Bandung basin are prone to flooding. This study offers an effective and efficient method of mapping flood-prone areas based on floo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Research conducted in Indonesia by Yulianto et al (2018), who attempted to observe inundated areas using Landsat-8 multitemporal images in Bandung basin, found that MNDWI was the most appropriate parameter to use to detect flooded areas in the Bandung basin which had heterogeneous land surface conditions. In other studies, by using Landsat-7 ETM+ image data, the extent of inundated areas caused by floods in lowland regions could be identified and separated based on NDWI, MNDWI, and NWI.…”
Section: Resultsmentioning
confidence: 99%
“…Research conducted in Indonesia by Yulianto et al (2018), who attempted to observe inundated areas using Landsat-8 multitemporal images in Bandung basin, found that MNDWI was the most appropriate parameter to use to detect flooded areas in the Bandung basin which had heterogeneous land surface conditions. In other studies, by using Landsat-7 ETM+ image data, the extent of inundated areas caused by floods in lowland regions could be identified and separated based on NDWI, MNDWI, and NWI.…”
Section: Resultsmentioning
confidence: 99%
“…In this area, there is also a meeting location of Citarik river with its tributaries; those are Cimande river and Cikijing river. Such a river meeting area is prone to flooding as happened in floods in the Melong village of Cimahi city in the branch area of Cilember and Cibeureum river with Citarum river [16]. The meeting cross-section of Cisangkan river and Citarum river is in Leuwigajah Village, Cimahi City.…”
Section: The Materials and Methodsmentioning
confidence: 99%
“…is was done because noise cannot distinguish between water and darker pixel (nonwater) surfaces, such as the shadow. Implementation of several indices of such water has been used in various other aspects, such as analysis and flood monitoring [10][11][12], environment analysis [13], water surface mapping [14][15][16], water-quality assessment [17], and agriculture [18].…”
Section: Introductionmentioning
confidence: 99%